2019
DOI: 10.1007/s11596-019-2016-4
|View full text |Cite|
|
Sign up to set email alerts
|

Probiotic Therapy for Treating Behavioral and Gastrointestinal Symptoms in Autism Spectrum Disorder: A Systematic Review of Clinical Trials

Abstract: The therapeutic potentials of probiotics in autism spectrum disorder (ASD) remains controversial, with the only existing systematic review on this topic published in 2015. Results from new trials have become available in recent years, we therefore conducted an updated systematic review, to assess the efficacy of probiotics in relieving behavioral symptoms of ASD and gastrointestinal comorbidities. Our review includes two randomized controlled trials, which showed improvement of ASD behaviors, and three open tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 26 publications
(58 reference statements)
0
18
0
Order By: Relevance
“…The effectiveness of probiotic therapy is limited due to the use of bacterial strains known for their medicinal properties and omission of unknown and probably significant factors. However, probiotic supplementation is well tolerated and the serious adverse effects are infrequent, yet rarely evaluated (Liu et al, 2019b). After knowing the microbiota composition of an individual, it may be easier to choose pro-or prebiotic preparations or modify their composition in relation to patient's needs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effectiveness of probiotic therapy is limited due to the use of bacterial strains known for their medicinal properties and omission of unknown and probably significant factors. However, probiotic supplementation is well tolerated and the serious adverse effects are infrequent, yet rarely evaluated (Liu et al, 2019b). After knowing the microbiota composition of an individual, it may be easier to choose pro-or prebiotic preparations or modify their composition in relation to patient's needs.…”
Section: Discussionmentioning
confidence: 99%
“…Administration of probiotics aiming to restore gut microbial balance also seems to be promising (Saurman et al, 2020). The recent data on the therapeutic use of probiotics in ASDs revealed suggestive evidence and improvement trend in the behavioral and GI symptoms after the administration of these supplements (Liu et al, 2019b;Martıńez-Gonzaĺez and Andreo-Martıńez, 2020).…”
Section: Microbial-mediated Therapeutic Approaches In Asd With Comorbid Gimentioning
confidence: 99%
“…In the first stage (12 weeks), all the patients will be randomly assigned to two groups: group A (30 subjects) receives oral L. reuteri probiotics while group B (30 subjects) receives oral as a placebo. We decided on a 12-week timeline because according to the most recent systematic review of probiotics therapy in ASD, the average duration of clinical trials is 3 months [19]. In the second stage, subjects in group A and group B will continue their respective oral L. reuteri probiotics or placebo administration as in stage 1.…”
Section: Study Proceduresmentioning
confidence: 99%
“…Multiple studies have reported effects of probiotic treatments on microbiota composition and GI symptoms in ASD children. Although many of these studies did not analyze the behavior of the children, or did not see any improvement after probiotic administration [26,[119][120][121], other studies did report behavioral improvement [122][123][124][125]. In Shaaban et al (2017) [123], 30 children with ASD were given a 3-month, daily treatment with a patented probiotic mixture (composed of strains of the species L. acidophilus, L. rhamnosus and B. longum) which induced an improvement in communication, sociability and cognitive awareness, characterized by a decrease in the ATEC (autism treatment evaluation checklist) score.…”
Section: Clinical Studiesmentioning
confidence: 99%